Next-generation sequencing of 68 genes in sudden unexplained death of young individuals in forensics. (December 2015) - Buscemi, L.; Alessandrini, F.; Perna, G.; Tagliabracci, A.
Abstract: Sudden cardiac death in the young is a very dramatic event that occurs in apparently healthy individuals without an explainable cause of death. The advancement of knowledge in the field of molecular biology has suggested that genetic abnormalities are the leading cause of sudden unexplained death in young people. Three forensic SUD cases were studied. 68 genes most frequently associated with SUD were analyzed by NGS.